Inferior pedicle nasolabial flap in nasal ala reconstruction - Marcelo Rosseto; Daniel Nunes e Silva; Ana Luiza Ceolin Lyrio; Ana Lara Ceolin Lyrio; Antônio Cavichini Rosseto (Revista Brasileira de Cirurgia Plástica)
Introduction: The nasal alar has always been a major reconstructive diflculty, and in the search for a flap with skin characteristics similar to this one, we came across the inferiorly based nasolabial flap. The objective of this study was to demonstrate the viability of the proposed flap for reconstruction of the nasal alar after removal of skin tumors.Methods: This study analysed twenty cases of inferiorly based nasolabial flap performed with the same surgical technique in the period between 2008-2019 and followed up for one year of postoperative.Results: Of the 20 studied cases, 13 (65%) did not present complications, being the most described: partial defect coverage and partial disappearance of the nasolabial sulcus.Conclusion: The inferiorly based nasolabial flap proved to be a viable flap for nasal alar reconstruction due to the quality of the skin, easy execution, and minimal complication rates.